The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/ijnp/pyw001
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Related Immune Markers in Depression: Implications for Treatment

Abstract: Major depression is a serious psychiatric disorder; however, the precise biological basis of depression still remains elusive. A large body of evidence implicates a dysregulated endocrine and inflammatory response system in the pathogenesis of depression. Despite this, given the heterogeneity of depression, not all depressed patients exhibit dysregulation of the inflammatory and endocrine systems. Evidence suggests that inflammation is associated with depression in certain subgroups of patients and that those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 223 publications
(265 reference statements)
1
58
0
Order By: Relevance
“…The current study determined that the anti-depressant, Desip, was able to decrease DO and IFNγ expression in the brain (hippocampus, microglia and astrocytes) and the periphery (PBMCs). Since IFNγ is the most potent stimulator of Ido1 and Ido2 expression (Fatokun et al, 2013; Hughes et al, 2016), these data suggest that Desip can act by limiting IFNγ production, and thus, diminishing IFNγ-dependent Ido1 and Ido2 expression. However, our ex vivo work confirmed that Desip was able to directly decrease IFNγ–induced Ido1 and Ido2 expression by murine PBMC −T , T cells, OHSCs and human PBMCs.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The current study determined that the anti-depressant, Desip, was able to decrease DO and IFNγ expression in the brain (hippocampus, microglia and astrocytes) and the periphery (PBMCs). Since IFNγ is the most potent stimulator of Ido1 and Ido2 expression (Fatokun et al, 2013; Hughes et al, 2016), these data suggest that Desip can act by limiting IFNγ production, and thus, diminishing IFNγ-dependent Ido1 and Ido2 expression. However, our ex vivo work confirmed that Desip was able to directly decrease IFNγ–induced Ido1 and Ido2 expression by murine PBMC −T , T cells, OHSCs and human PBMCs.…”
Section: Discussionmentioning
confidence: 87%
“…As IFNγ is a potent inducer of Ido1 (Hughes et al, 2016) and Ido2 (Fatokun et al, 2013), we quantified IFNγ expression to determine if Desip decreases IFNγ to control DO expression. IFNγ expression was very low in astrocytes (and not induced, not shown) and not detected in OHSCs (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…83,85,88,89 Furthermore, chronic exposure to corticosteroids results in numerous cellular changes in the brain, and chronic stress is a strong risk factor for the development of anxiety, depression, addiction, and other psychological disorders. 80,83,86,90,91 GPR83 was discovered as being activated by the synthetic glucocorticoid dexamethasone, suggesting that GPR83 may be involved in the stress response, and indeed, knocking out GPR83 in mice leads to a stress protective phenotype. 52 Further research needs to be conducted regarding the role of the immune system in response to stress and the potential protective effects GPR83 may play centrally or peripherally.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 presents the possible role of IL-6 in MDD pathogenesis. Here, when encountering molecular pathogens or foreign antigen, monocytic immune cells respond by secreting cytokines including IL-6 [126]. Dendritic cells mature following antigen presentation, cytokine production and co-stimulation from the system, which in turn activates lymphocytes, such as T cells [126].…”
Section: Il-6 and The Mdd Pathogenesismentioning
confidence: 99%